Activation of hole charge carriers and generation of electromotive force in gabbro blocks subjected to nonuniform loading. Issue 3 (27th March 2013) - Takeuchi, Akihiro; Nagao, Toshiyasu
Abstract: [1] This study verifies the activation of hole charge carriers in gabbro under nonuniform loading, which has been proposed as the possible source of the stress‐induced electromotive force in dry rocks without piezoelectric effect. When one end of vacuum‐dried gabbro blocks was subjected to uniaxial loading, the unloaded end became electronically positive (+80 mV at 50 MPa). The Seebeck coefficient of the loaded volume decreased from ~15.8 mV/K to ~14.9 mV/K when loaded, while the Seebeck coefficient of the unloaded end did not change remarkably (~15.6 mV/K). This means that this gabbro originally included a small number of hole charge carriers and the carriers in the loaded volume increased when loaded. From the viewpoint of the fundamental band model of solid state, the most reasonable mechanism of the increment is the decrease of the energy gap between the acceptors and the valence band top. Based on this idea, a generation model of the stress‐induced electromotive force is proposed. Since this model is expected to be universally applicable to various types of rocks, similar electromotive forces in the crustal scale may be induced by seismic, volcanic, and tidal activities.